Training primary student teachers for CLIL: innovation through collaboration - Delicado Puerto, Gemma; Pavón Vázquez, Víctor (Pulso. Revista de educación, 2016)
The escalating number of bilingual schools in Spain has provoked an unsustainable demand of field professionals. As a result, higher education is implementing bilingual teacher training programs at the bachelor level, which are aimed at preparing primary education teachers for bilingual contexts. These degrees usually train prospective educators from a linguistic standpoint and may not guide students in methodological principles that promote successful integration of subject and language work. A shift of focus on the training of these future teachers could be adopted based on the development of student teachers’ linguistic and methodological professional capacities in order to qualify them to be successfully incorporated in a bilingual professional context. This study analyzes the implementation of a framework of collaboration between university teachers and experienced bilingual teachers. The data extracted from the opinions of the participants have resulted in a comprehensive approach constructing bilingualism on an expanded collaborative philosophy. The results obtained from the over-all experience point to the benefits of incorporating in-service teachers in the training of future bilingual teachers through the establishment of a sustainable connection in higher education
Keywords: Bilingual Education; CLIL; Teacher Training; Teacher Collaboration; Pedagogy